1986
DOI: 10.1152/ajpendo.1986.251.1.e78
|View full text |Cite
|
Sign up to set email alerts
|

Hormones in perinatal rat and spiny mouse: relation to altricial and precocial timing of birth

Abstract: Rat (Rattus norvegicus) and spiny mouse (Acomys cahirinus) are closely related murine species that, due to their altricial (rat) and precocial (spiny mouse) modes of development, differ in the developmental timing of birth. A comparison between the developmental profiles of plasma glucagon, insulin, thyroxine, triiodothyronine, and glucocorticosteroid hormone was carried out to elucidate the question to what extent these hormonal profiles were related to the timing of birth. Although corticosterone is the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
1
30
1
Order By: Relevance
“…When all tests had been completed, experimental animals were weighed again, then culled, measured and autopsied as above, and a final sample of blood (terminal sample) taken by cardiac puncture. All serum samples were later analysed for testosterone and cortisol (the major glucocorticoid in Acomys (Lamers et al, 1986)) concentrations using ASD (USA) ELISA kits.…”
Section: Intruder Exploration and Interaction Testsmentioning
confidence: 99%
“…When all tests had been completed, experimental animals were weighed again, then culled, measured and autopsied as above, and a final sample of blood (terminal sample) taken by cardiac puncture. All serum samples were later analysed for testosterone and cortisol (the major glucocorticoid in Acomys (Lamers et al, 1986)) concentrations using ASD (USA) ELISA kits.…”
Section: Intruder Exploration and Interaction Testsmentioning
confidence: 99%
“…Specifically, we investigated whether the consequences for the placenta of excess maternal glucocorticoids would differ depending on the sex of the fetus, the region of the placenta examined, and/or the time elapsed after glucocorticoid exposure. In order to undertake this study, we used the spiny mouse, a rodent species in which the natural circulating glucocorticoid is cortisol [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have previously shown that maternal stress at mid-pregnancy can alter the brain development and behavioural outcomes in the offspring of the spiny mouse [37], and transient maternal glucocorticoid administration at mid-pregnancy, but not late pregnancy in this species, decreases the expression of the P450c17 enzyme in the adrenal gland, as well as decreasing systemic DHEA concentrations [36]. As mentioned above, although data are available for laboratory rat and mouse strains, there are no reports of DHEA biosynthesis in the brain of the spiny mouse, a species born after a relatively long gestation of 39 days [38], when the offspring show advanced development of the cerebral cortex compared with conventional rodents [39]. We hypothesize that the significance of the extended gestation in this species may be to promote mechanisms such as the neurotrophic and anti-glucocorticoid actions of DHEA that protect the fetal brain against high concentrations of glucocorticoids, whether this is of fetal or maternal origin.…”
Section: Introductionmentioning
confidence: 99%